Project Management of Water Treatment Plant - Pravin Manatkar, Sunil Thakare, Abhishek Shirle, Satish S. Deshmukh (Mathematical Statistician and Engineering Applications, 2022)
Increasing urban population, especially in developing nations, both land and water are under extreme stress; it also causes too much water, many things that cannot be done. Therefore, water purification has become necessary due to the scarcity of drinking water and the needs of the growing world population. The use of water directly from rivers, streams and lakes is not safe today because it contains many diseases, viruses and other diseases that can affect human, plant and animal health. This weak and unsafe water source creates the need for water treatment plants. This study aims to evaluate project management practices for the construction of a 5 capacity water treatment plant.5 MLD is used to supply potable water to 30 villages in Shegaon, Maharashtra. Therefore, the responsibilities of project management include identifying business needs, making business decisions, monitoring progress, and correcting business gaps. The aim is to complete the project plan for the construction Treatment of water facilities by means of planning and carrying out and managing time, money, people and resources. The data for this study were obtained through interview questions from project managers, engineers, contractors, customers and site workers, and qualitative questions from people experienced in business and business development. This study aims to understand the water treatment plant construction project management application, evaluation and modification knowledge.